Pilot-Scale Selenium Bioremediation of San Joaquin Drainage Water with Thauera selenatis - Cantafio, A. W. (1996)
This report describes a simple method for the bioremediation of selenium from agricultural drainage water. A medium-packed pilot-scale biological reactor system, inoculated with the selenate-respiring bacterium Thauera selenatis, was constructed at the Panoche Water District, San Joaquin Valley, Calif. The reactor was used to treat drainage water (7.6 liters/min) containing both selenium and nitrate. Acetate (5 mM) was the carbon source-electron donor reactor feed. Selenium oxyanion concentrations (selenate plus selenite) in the drainage water were reduced by 98%, to an average of 12 (plusmn) 9 (mu)g/liter. Frequently (47% of the sampling days), reactor effluent concentrations of less than 5 (mu)g/liter were achieved. Denitrification was also observed in this system; nitrate and nitrite concentrations in the drainage water were reduced to 0.1 and 0.01 mM, respectively (98% reduction). Analysis of the reactor effluent showed that 91 to 96% of the total selenium recovered was elemental selenium; 97.9% of this elemental selenium could be removed with Nalmet 8072, a new, commercially available precipitant-coagulant. Widespread use of this system (in the Grasslands Water District) could reduce the amount of selenium deposited in the San Joaquin River from 7,000 to 140 lb (ca. 3,000 to 60 kg)/year.